QUALITY OF MEDICAL SERVICES: ESSENCE AND TOOLS TO ENSURE IT - Kinash , I. P.; Savchuk , L. M. (The actual problems of regional economy development, 2023)
The article is aimed at studying the essence of the concept of "quality of medical services" and the peculiarities of using tools to ensure it in a medical institution. The following research methods were used: scientific observation, abstract and logical analysis, generalisation and descriptive method. The article summarises the position of scholars on the concepts of "quality", "medical service", and "quality of medical service". It is found that the criteria for the quality of medical services are specific in terms of their properties and characteristics. The specificity of medical services is manifested in the following features: imperceptibility, inseparability from the source of provision, unsustainability, and inconsistency of quality. The quality of healthcare services is considered to be the main target function and, at the same time, a criterion of the healthcare sector. The most characteristic features of medical services are summarised. It is found that medical services are very specific and have the following features: intangibility; inseparability from the source of provision; quality variability; and unsustainability. It is emphasised that the quality of medical services reflects the ability to meet the needs of the consumer and his/her expectations. Quality can be assessed by taking into account two components: consumer satisfaction with the process of healthcare provision and consumer satisfaction with the outcome of healthcare provision. Therefore, the balanced and reasonable use of quality assurance tools for healthcare services is important both from the perspective of society as a whole and from the perspective of individual business entities. The object of the study was the municipal non-profit enterprise "Central City Clinical Hospital of Ivano-Frankivsk City Council". It is found that the activities to ensure the quality of medical services are aimed at both clinical and organisational aspects. The main tools for ensuring the quality of medical services are: accreditation, standardisation, licensing and compliance with the protocol for each disease. The results of applying these tools are summarised. A positive result is revealed - the quality of medical services has been improved both in the examination and in the treatment of patients.